International law of the sea - Eishan Jan, Mohammad Naqib (2016)
This paper discusses an important aspect of public international law that governs the vast oceans of the world, covering three fourths of the planet earth. It explains the the natural resources of the seas, ships that are sailing on the seas and protection and preservation of the marine environment.